(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
Processors are two types arithmetic processors and signal processing processors. Arithmetic and Logic Unit(ALU) is used in the arithmetic processors where as Multiplier Accumulator Content (MAC) is used in signal processing processors like DSP processors. In ALU adders play a major role not only for addition but also in performing many other basic arithmetic operations like subtraction, multiplication, increment / decrement etc. Thus, realizing an efficient adder is required for better performance of a processor and ALU in particular [1,2].